Effectiveness of Micropulse MP3 Cyclodiode Laser in controlling Intraocular pressure without Acetazolamide - Wasim, Sahira; Ghayoor, Imran; Shakir, Munira; Zafar, Shakir (Pakistan Journal of Ophthalmology, 2020)
ABSTRACT Background: Glaucoma is a 2ndleading cause of irreversible blindness worldwide. Primary surgical procedures include trabeculectomy with or without anti-metabolites, as well as glaucoma drainage devices. Cycloablation lowers IOP by destruction of ciliary body epithelium and stroma, thus reducing aqueous production. Objective: To determine effectiveness of micropulse mp3 cyclodiode laser in controlling intraocular pressure without acetazolamide. Study design: Descriptive case series study Place and duration of study: Department of Ophthalmology, Liaquat National Hospital, Karachi for 6 months duration Material and Methods: In our study total 98 patients of either gender with age 20 to 50 years, following inclusion criteria (Chronic open angle glaucoma, Neovascular, Refractory, Uveitic, Trauma induced glaucoma, and Post vitrectomy induced glaucoma) and exclusion criteria (Primary angle closure and Normal tension glaucoma) were included. Descriptive statistics were calculated. Frequencies and percentages were computed for qualitative variables. Quantitative variables were presented as mean±standard deviation. The mean baseline IOP was compared with mean IOP of 3 months using student t-test. Effect modifiers were controlled through stratification. Fisher exact test was used to see the association of effectiveness with stratified groups. P-value ?0.05 was considered as significant. Results: Among total 98 patients, 63.3% were male and 36.7% were female. Mean age was 48.46±13.39 years. The effectiveness of Micropulse Mp3 Cyclodiode Laser was observed in 85.7% cases. Significant mean difference was found for pre-op IOP with IOP after 3 months for right eye and left eye. Insignificant association of effectiveness was found with gender, age, type and procedure. Conclusion: Micro pulse MP3 appears to be a promising, safe alternative procedure with potential advantages as well as high level of effectiveness. Keywords: Micropulse Mp3 Cyclodiode Laser, Intraocular Pressure, Acetazolamide